PEMBELAJARAN MENYIMAK LANJUTAN DI SEKOLAH DASAR - Qalbi, Nur; Hamzah, Rahma Ashari; Imelda, Imelda (Universitas Tanjungpura, 2025)
Listening is one of the fundamental language skills that significantly influences students' language comprehension and communication abilities. In elementary school, advanced listening instruction is often overlooked, resulting in students